Studi Literatur: Tata Kelola Kurikulum di Belanda: Ketegangan antara Otonomi Sekolah, Standardisasi Nasional, dan Ekuitas Pendidikan - Widayaningsih, Widayaningsih; Mulyono, Mulyono; Waluya, St. Budi (Papanda, 2026)
This study aims to analyze curriculum governance in the Netherlands, which is characterized by strong school autonomy as guaranteed under Article 23 of the Dutch Constitution. The focus of this study is to examine the implications of this constitutional freedom for the coherence of national curriculum policy, as well as the state's efforts to ensure educational quality and equity. The research employed a qualitative approach through document study and policy analysis of educational regulations, official government reports, and relevant scholarly literature. Data analysis was conducted using content analysis techniques through thematic coding to identify policy patterns and systemic implications for curriculum implementation. The findings were validated through source triangulation by comparing data across policy documents and academic literature to ensure credibility. The results indicate that school autonomy provides space for pedagogical innovation and diversity in instructional approaches. However, it simultaneously generates curriculum fragmentation, weak coherence across educational levels, and reinforces social inequality through early academic tracking mechanisms. Curriculum reform through the Curriculum.nu program has encountered structural and legal constraints in its implementation due to the limited authority of the central government. This study concludes that curriculum reform in the Netherlands must be accompanied by strengthened governance mechanisms and evaluation systems in order to achieve sustainable coherence and educational equity.